Pelatihan Penyusunan Bahan Ajar Bermutu Berbantuan Artificial Intelligence pada Guru Sekolah Dasar Kota Madiun - Parji, Parji; Yuhanna, Wachidatul Linda; Prayitno, Trio Ageng (Jurnal SOLMA, 2026)
Background: Improving the quality of learning in elementary schools depends heavily on teachers' ability to develop high-quality, innovative, and student-centered teaching materials. Observations indicate that many elementary school teachers in Madiun City still face challenges in developing high-quality teaching materials, due to limited time, creativity, and a lack of understanding of the ideal standards for developing such materials. Elementary school teachers in Madiun City require comprehensive training. The purpose of this training is to implement and analyze the effectiveness of a training program for developing high-quality AI-assisted teaching materials that meet the needs of elementary school teachers. Method: This community service program is implemented by UNIPMA lecturers. The target participants are 50 elementary school teachers in Madiun City. This community service program uses a two-month participatory approach through four stages: outreach, training in developing teaching materials, training in using AI, and monitoring and evaluation. Results: The data showed that 96% of teachers understood the concept of developing high-quality teaching materials, 94% could use AI applications to create digital textbooks, and 92% expressed satisfaction with the community service team's service. Conclusions: The implementation of AI-assisted training to develop high-quality teaching materials was effective in improving teachers' competence while also encouraging more creative, adaptive learning aligned with the demands of 21st-century education.